Intercultural Dynamics in English Language Learning at Islamic Schools: Impacts on Student Islamic Identity Construction in a Culturally Pluralistic Context - Ghufron, M. Ali; Taufiq, Ahmad; Firdaus, Ali Usman (Universitas Pendidikan Ganesha, 2024)
The dynamics of intercultural communication and language acquisition are very important in Islamic schools, where English language learning intersects with the formation of students' Islamic identity. This study aims to analyze the intercultural dynamics in English language learning in Islamic schools and its impact on the construction of students' Islamic identity in a pluralistic cultural context. This study uses a qualitative approach with a case study method. The subjects of this study were students in grades X, XI, and XII in four selected schools, as well as English teachers who teach in these classes. Then, for in-depth interviews, subjects were selected purposively. The data for this study were collected through in-depth interviews and questionnaires. The research data were analyzed using thematic analysis. The results of the thematic analysis of the data indicate that students face significant intercultural challenges, including linguistic barriers, cultural misunderstandings, and limited exposure to English outside the classroom. These challenges often create tensions as students try to balance the pressure to adopt a global identity and maintain their local cultural and religious values. The findings of this study indicate that although most students considered the impact of English language learning on their Islamic identity to be neutral (having neither positive nor negative effects), a number of students experienced positive reinforcement or potential conflict in their identity construction.